Revisiting a Genre: Teaching Infographics in Business and Professional Communication Courses. Issue 4 (December 2013) - Toth, Christopher
Infographics exist on nearly any topic you can imagine, proliferating in the digital age with social media. As this genre continues to explode in the business scene, business and professional communication instructors can no longer ignore showing their students infographics. After first defining the genre and outlining how it situates itself within business and professional communication, this article offers two approaches to increase awareness and exposure of infographics for students. The first focuses on an analysis assignment using infographics; the second focuses on a production assignment.